Implementasi Game Math Puzzle sebagai Media Pembelajaran Numerasi Siswa SDN 02 Badrain - Nurhadiani, Rina; Alifa, Siti; Aisy, Rihadatul; Satira, Satira; Katrunada, Saskia; Humaela Rizka, Siti; Chandra Dewi, Alfiana; Dwi Astuti, Silvia (Pendidikan Matematika, FKIP Universitas Mataram, 2024)
School with relatively low literacy and numeracy skills are an indicator of where campus teaching programs are held. Therefore, students from the Faculty of Teacher Training and Education at the University of Mataram who were registered as campus teaching participants for grade 6th placement at SDN 02 Badrain created the